Description of extreme Gibbs measures for the Ising model with three interactions - Ganikhodjaev, Nasir; Akin, Hasan; Uguz, Selman; Temir, Seyit (Polish Academy of Sciences Publishing House, 2013)
In this paper, we consider an Ising model with three competing interactions (nearest neighbor, next-nearest neighbor, and ternary prolonged neighbor) on the Cayley tree of order two, investigated by Ganikhodjaev et al. We study translation-invariant Gibbs measures of the Ising model with these competing interactions. Also, we investigate the set of the extreme Gibbs measures called Markov random elds with memory 2 of the model.